Isolation of SARS-CoV-2-blocking recombinant antibody fragments and characterisation of their binding to variant spike proteins - Antoine, Delphine; Mohammadi, Moein; McDermott, Chloe E.; Walsh, Eithne; Johnson, Patrick A.; Wawrousek, Karen E.; Wall, J. Gerard (Frontiers in Nanotechnology, 2022)
COVID-19 is a severe acute respiratory disease caused by SARS-CoV-2. From its initial appearance in Wuhan, China in 2019, it developed rapidly into a global pandemic. In addition to vaccines, therapeutic antibodies play an important role in immediately treating susceptible individuals to lessen severity of the disease. In this study, phage display technology was utilised to isolate human scFv antibody fragments that bind the receptor-binding domain (RBD) of SARS-CoV-2 spike protein. Of eight RBD-binding scFvs isolated, two inhibited interaction of RBD with ACE2 protein on VeroE6 cells. Both scFvs also exhibited binding to SARS-CoV-2 Delta variant spike protein but not to Omicron variant spike protein in a Raman spectroscopy immunotest. The study demonstrates the potential of recombinant antibody approaches to rapidly isolate antibody moieties with virus neutralisation potential.